A comparison of ACL reconstruction using patellar tendon versus hamstring autograft in female patients: a prospective randomised study - Kautzner, Jakub; Kos, Petr; Hanus, Martin; Trc, Tomas; Havlas, Vojtech (International orthopaedics, 2015)
PURPOSE: The incidence of an anterior cruciate ligament (ACL) tear is highest in female patients; however, it is not apparent whether graft choice affects clinical results. The aim of this prospective randomised study was to evaluate clinical results of an ACL reconstruction using patellar tendon [bone-patellar tendon-bone (BTB)] or hamstring graft (HS) in female patients. METHODS: Inclusion criteria were traumatic instability, no signs of osteoarthritis, no previous instability and no contralateral knee instability. Inclusion criteria were met in 150 patients, mean age 26 (17-47) years. Patients were randomised into two groups of 75 patients according to graft type; all had the same rehabilitation protocol. Tegner Lysholm knee score and stability were evaluated pre-operatively and one and two years postoperatively. The difference between groups was statistically evaluated using unpaired t test. RESULTS: Of the 150 patients, all completed one year follow-up; three were lost to follow-up at two years. There was no significant difference in functional scores and knee stability between groups. The HS group had significantly less anterior knee pain in the first six months postoperatively. CONCLUSION: ACL reconstruction significantly improves clinical results and stability of the knee. Difference in Lysholm score and stability between groups was not significant. Neither group showed higher tendency to graft failure within two years. Graft choice for reconstruction in female patients should be surgeon specific and individualised, as both grafts studied achieved comparable results.
Keywords: dospělí; kosterní svaly; Female; ligamentum cruciatum anterius; Adult; výsledek terapie; mladý dospělý; nestabilita kloubu; ženské pohlaví; Anterior Cruciate Ligament; Knee Joint; Adolescent; Tendons; poranění předního zkříženého vazu; lidé; autologní transplantace; Treatment Outcome; Muscle, Skeletal; šlachy; rekonstrukce předního zkříženého vazu; Anterior Cruciate Ligament Reconstruction; Humans; prospektivní studie; Anterior Cruciate Ligament Injuries; ligamentum patellae; Knee Injuries; Prospective Studies; Young Adult; poranění kolena; Autografts; Patellar Ligament; Joint Instability; lidé středního věku; Transplantation, Autologous; kolenní kloub; Middle Aged; mladiství; autologní štěp